John MURTAGH'S general practice COMPANION HANDBOOK - Murtagh, John 1936-; Murtagh, Clare (McGraw-Hill Education (Australia) Pty Limited, 2022)
Annotation. John Murtagh's General Practice is widely recognised as the gold standard reference for general practice and primary health care. Its emphasis on the importance of clinical reasoning,early diagnosis and treatment makes this the essential reference for medical students, trainees and general practitioners. Presented in alphabetical order and in a convenient pocket-sized format, John Murtagh's General Practice Companion Handbook 8e summarises key content from the main book. It is an accessible, trusted and portable source of information for medical students and experienced professionals.